PENGENALAN PROFESI APOTEKER DAN PENYULUHAN PEMANFAATAN DAUN TEMPUYUNG SEBAGAI OBAT BATU GINJAL DI SMA NEGERI 1 NAMORAMBE - Sulasmi Sulasmi Sulasmi (INSTITUT KESEHATAN DELI HUSADA, 2023)
Health is a valuable asset for every human being. No exception for other living things. Healthy is a condition that indicates that the body is free from disease. A person is said to be unhealthy if one of his organs or body has decreased function or can also be infected by bacteria, parasites, viruses and other organisms. Kidneys can be said to be the center of the whole body, if damaged it can affect other organs in the body. One of the disiases of the kidney is kidney stones. Kidney stone disease is the formation of hard material resembling stones derived from minerals and salts in the kidneys. Alternative therapy is an option in dealing with kidney stones by using the medicinal plant tempuyung leaves which contain potassium which plays a role in the decay of kidney stones. Utilization of tempuyung leaves as a medicine for kidney stones is processed in the form of the brew from tempuyung leaves. PKM activities are carried out using the counseling method with the target of this activity being students at SMA N 1 Namorambe who will also be able to play a role in increasing family and community knowledge related to the use of conventional and traditional medicine that is good and can utilize plants as medicine. The implementation of this activity goes through the stages of Preparation, Implementation and Evaluation. PKM activities carried out to students at SMA N 1 Namorambe are effective in increasing community knowledge and improving public health status.